Binocular advantages in reading revisited: attenuating effects of individual horizontal heterophoria - Stephanie Jainta; Joelle Joss (Journal of Eye Movement Research)
Reading with two eyes necessitates efficient processes of binocular vision, which provide a single percept of the text. These processes come with a binocular advantage: binocular reading shows shorter average fixation durations and sentence reading times when compared to monocular reading. A couple of years ago, we showed for a small sample (N=13) that binocular advantages critically relate to the individual heterophoria (the resting state of vergence). In the present, large-scale replication we collected binocular eye movements (Eyelink II) for 94 participants who read 20 sentences monocularly and 20 sentences binocularly. Further, individual heterophorias were determined using three different optometric standards: objective eye tracking (EyeLink II at 60 cm), Maddox wing test (at 30 cm) and measures following the “Guidelines for the application of the Measuring and Correcting Methodology after H.-J. Haase” (MCH; at 6 m). Binocular eye movements showed typical pattern and we replicated (1) binocular advantages of about 25 ms for average fixation durations and (2) a reduction in binocular advantages when heterophoria increased – but only when heterophoria was identified by EyeLink II or Maddox wing measures; MCH measures of heterophoria did not affect binocular advantages in reading. For large heterophorias binocular reading even turned into a disadvantage. Implications for effect estimations and optometric testing will be discussed.